Expression of individualism – collectivism in verbal insults - Kurapov, Anton; Ishchenko, Alexander; Tyelcharov, Alexander (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
Abstract It is well known that many cultures in the modern world are characterized by such polar constructs as individualism and collectivism. Western world is generally perceived as much more individualistic, on the contrary, Eastern world is perceived as much more collectivistic. However, civilizational identity of Ukraine is not sufficiently defined due to the specific historical development, since it has always been between East and West. Semin and Rubini (1990) proposed a study of the manifestations of individualism and collectivism through the analysis of verbal abuse that are common for a specific nationality. In our opinion, this method will identify the most current tendency for Ukrainians. For comparison, the results of a study conducted in Finland, Sweden and Poland were also presented. Thus, according to a study, Ukrainians are more likely to express individualism in 3 comparison to the expression of collectivism. The same applies to other studied groups.